Determination of the chemical composition and antimicrobial activity of Frankenia hirsuta (Bangladesh Journal of Pharmacology, 2017)
Frankenia hirsuta is widely located in Turkey, but the antimicrobial potential and biochemical composition analysis of it weren’t determined yet. By using the disk diffusion method, the susceptibility of 17 bacteria and 1 fungi were analyzed, which included Bacillus, Candida, Enterobacter, Enterococcus, Escherichia, Klebsiella, Listeria, Pseudomonas, Salmonella and Staphylococcus genera. 0.8, 1.5 and 3.1 mg of samples were prepared by using absolute ethanol. The bioactive composition of the plant extract was determined by gas chromatography-mass spectroscopy, and National Institute of Standards and Technology library was used for the mass spectra analysis. The results showed that F. hirsuta had antimicrobial activity against all of the studied micro-organisms except E. aerogenes and E. coli. Several active metabolites were identified, but some composition of this sample didn’t match with the library. These results are the first report for the antimicrobial potential and biochemical composition of F. hirsuta.Video Clip of Methodology:3 min 36 sec:   Click to watch